Barriers and Proposed Solutions to a Successful Implementation of Pediatric Sepsis Protocols - Medeiros, Daniela Nasu Monteiro; Shibata, Audrey Ogawa; Pizarro, Cristiane Freitas; Rosa, Maria de Lourdes Alves; Cardoso, Marta Pessoa; Troster, Eduardo Juan (Frontiers in Pediatrics, 2021)
The implementation of managed protocols contributes to a systematized approach to the patient and continuous evaluation of results, focusing on improving clinical practice, early diagnosis, treatment and outcomes. Advantages to the adoption of a pediatric sepsis recognition and treatment protocol include: a reduction in time to start fluid and antibiotic administration, decreased kidney dysfunction and organ dysfunction, reduction in length of stay and even a decrease on mortality. Barriers are: absence of a written protocol, parental knowledge, early diagnosis by healthcare profissionals, venous access, availability of antimicrobials and vasoactive drugs, conditions of work, engagement of healthcare profissionals. There are challenges in low-middle income countries (LMIC). The causes of sepsis and resources differ from high-income countries. Viral agent such as dengue, malaria are common in LMIC and initial approach differ from bacterial infections. Some authors found increased or no impact in mortality or increased length of stay associated with the implementation of the SCC sepsis bundle which re-inforces the importance of adapting it to most frequent diseases, disposable resources, and characteristics of healthcare professionals. Conclusions: 1) be simple; 2) be precise; 3) education; 4) Improve communication; 5) work as a team; 6) share and celebrate results.